Insights into the diversity of cow milk production systems on the fringes of coastal cities in West Africa - Yassegoungbe, Fifame Panine; Oloukoi David, David; Aoudji, Augustin K. N.; Dossa, Luc Hippolyte; Schlecht, Eva (My University, 2022)
In sub-Saharan Africa, rapid population growth, urbanization, increasing incomes, and changing dietary preferences are the main drivers of the rising demand for livestock products, especially fresh milk and derived products. To meet this demand, there is an increasing number of dairy cattle farms in the densely populated coastal zone of Benin, where the country's largest city and commercial capital Cotonou is located. To identify and characterize the peri-urban dairy production systems in this region, 190 cattle keepers were surveyed, using the snowball sampling method, in four municipalities neighboring Cotonou. Information on their socio-economic characteristics, cattle herd sizes, and herd management practices were collected through questionnaire-based face-to-face interviews. Factor analysis of mixed data followed by hierarchical clustering on principal components, implemented in R statistical software, were applied to classify the surveyed farms into homogeneous groups. Results revealed six types of peri-urban dairy cattle farms differing mainly in their cows' breeds, herd sizes, and daily amount of milk produced. Most herds (88%) were owned by urban dwellers, mainly civil servants and traders, who entrusted the management of their cattle to hired professional herders. Irrespective of farm type, cows were of local taurine (65%) or Sahelian zebu (35%) breeds and were exclusively fed on communal natural pasture. Mineral supplementation was provided to the animals on 42% of farms, with significant variation across farm types. About 45% of the farms integrated cattle production with other agricultural activities, including coconut plantations (22%), where cow manure was used as fertilizer. The herd structure was similar across farm types, with average proportions of cows and heifers ranging from 37.6 to 47.5% and from 13.1 to 19.7%, respectively. With significant differences across farm types, the produced milk was either transformed into traditional cheese (32% of farms) or sold raw (85%). Milk and cheese sales represented 84% of the total farm income for three out of the six farm types. In the current context of rapid urbanization, communal grazing lands alone cannot provide sufficient feed to support increased milk production. In addition to improved feeding strategies, herd structure should be balanced in terms of the ratio between milk-producing and non-producing animals.
Keywords: Bovin; lait; périurbain; Sud Bénin